The RELATIONSHIP OF MINIMALIST LOGO REDESIGN AND GENERATION Z’S PURCHASE INTENTION: The MEDIATING ROLE OF BRAND AWARENESS AND BRAND PERCEPTION - Edang, Johann; Arce, Claire Anne A; Sanchez, Cyrin Francesca Y; Bandojo, Agnes Jocelyn P; Etrata, Antonio E (Journal of Business Studies and Management Review, 2024)
For the past decade, minimalism re-emerged as the dominant art movement, influencing multiple aspects of daily life, and there had been an observable trend among brands to transition to more minimalist-looking logos. The study analyzed the relationship between the minimalist logo redesign of Burger King and purchase intention, as mediated by brand awareness and brand perception. A quantitative research method was followed, and a descriptive-correlational analysis was used. The researchers utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). The study used convenience sampling, and based on the Cohen Statistical Power Analysis, 303 respondents were gathered for this study. The subject of this study was Generation Z, aged between 18 and 26 years old and residing in the National Capital Region, who should be keen and particular about visual elements and have constant exposure to brands. The results indicated that minimalist logo redesign significantly affects Generation Z’s brand awareness and brand perception. Furthermore, the findings showed that both mediating variables, brand awareness and brand perception, significantly affect purchase intention. With the trend of redesigning to minimalist logos, businesses, regardless of size, must assess their recognizability and memorability and evaluate their information accessibility. Brand managers can assist in raising awareness by exposing consumers to the redesigned logo in all of their brands’ marketing collateral. Furthermore, aligning the purpose and story behind the redesigned minimalist logo with the brand’s values can significantly improve the creation of positive brand perceptions.